The Morphological and Dynamic Changes of Ultrasound in the Evaluation of Effects of Oral Steroids Treatment for Patients with Carpal Tunnel Syndrome - Yun-Chain Yau; Chun-Pai Yang; Ching-Po Lin; I-Ju Tsai; Ching-Mao Chang; Cheng-Chia Yang; Po-Hsuan Shih; Yin-Yin Liao (Diagnostics, 2021)
The role of oral steroids in carpal tunnel syndrome (CTS) remains elusive. This study aims to depict the ultrasound findings and conceivable mechanisms in relation to the efficacy of oral steroids for patients with CTS by measuring the morphological and motion changes in the median nerve. In this study, CTS patients were randomized to the oral steroid group (14 participants and 22 wrists) or nicergoline group (22 participants and 35 wrists) for 4 weeks. Both treatment arms were given global symptom score (GSS) measurements and completed an ultra-sound at baseline and at 2- and 4-weeks post-treatment. In the nerve conduction study (NCS), distal motor latency (DML) was used to assess the treatment response at baseline and 4 weeks post-treatment. The cross-sectional area (CSA) and amplitude (AMP) evaluated by the maximum lateral sliding displacement represented the morphological and dynamic changes in the median nerve, respectively. The results showed that AMP, CSA, GSS, and DML were significantly im-proved in the steroid group, as compared to the nicergoline group at weeks 2 and 4 (p < 0.05). The mean improvement in ultrasound parameters CSA (15.03% reduction) and AMP (466.09% increase) was better than the DML (7.88% reduction) parameter of NCS, and ultrasound changes were detectable as early as 2 weeks after oral steroid administration. Ultrasounds can serve as a tool for the quantitative measurement of treatment effects and can potentially elucidate the pathogenesis of CTS in a non-invasive and more effective manner.